Method for manufacturing α-alumina powder
Patent Information
- Application Number
- KR1020247024406
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-30
- Filing Date
- 2023-03-28
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-03-28
Smart Images

Figure 112024078605545-PCT00001 
Figure 112024078605545-PCT00002 
Figure 112024078605545-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing α-alumina powder. Background Technology
[0002] α-alumina (Al2O3) is chemically stable and has excellent heat resistance, corrosion resistance, wear resistance, and insulation properties, as well as high strength and hardness. Taking advantage of these characteristics, α-alumina powder is widely used for various applications such as structural members, tools, abrasives, fillers, spark plugs, insulators, electronic circuit boards, and refractories.
[0003] In particular, taking into account the high chemical stability, electrical insulation, and thermal conductivity of α-alumina, α-alumina powder is used as a heat dissipation filler. Specifically, alumina powder is filled into a resin or rubber to form a resin composition, and the resin composition itself or a molded body of the resin composition is applied to products such as heat dissipation sheets, optical pickup components, heat dissipation grease, potting agents for circuit boards, tapes or components with heat dissipation properties, various injection molded products, sealants for motors or ICs, or copper-clad laminated boards.
[0004] However, industrially used alumina is mainly manufactured by the Bayer process. In the Bayer process, alumina powder is extracted by treating bauxite, an aluminum ore, with a high-temperature solution of caustic soda (sodium hydroxide). Next, the extraction residue is separated, and then a seed is added to the resulting sodium aluminate solution to precipitate aluminum hydroxide (Al(OH)3) crystals. After separating and washing the aluminum hydroxide, alumina is obtained by calcining at a temperature of 1000°C or higher. The Bayer process has the advantage of being able to manufacture alumina powder at a low cost.
[0005] However, alumina powder produced by the Bayer process generally contains impurities derived from the raw materials and the manufacturing process. For example, since caustic soda is used during production, sodium (Na) remains in the alumina powder. Additionally, the raw material bauxite contains calcium (Ca) as an impurity. Furthermore, in the Bayer process, calcium compounds such as slaked lime are often added to decompose the sodium carbonate accumulated in the sodium aluminate solution. Consequently, the resulting alumina powder contains calcium (Ca) or sodium (Na) as impurities.
[0006] Such impurities often pose a problem when alumina powder is applied to products. In particular, when used as a heat dissipation filler in resins or rubber, there is a risk of degrading electrical properties, such as insulation. For example, polyvinyl chloride (PVC) resin containing fillers is widely used as an insulating material for electric plugs. If the filler contains a large amount of calcium (Ca), chlorine generated by the thermal degradation of the PVC resin may react and combine with the calcium in the filler. If such a reaction occurs, the insulation properties of the material deteriorate, and in some cases, it may cause a fire. Furthermore, when epoxy resin containing fillers is used to construct printed circuit boards or semiconductor devices, if the filler contains a large amount of impurities such as calcium or sodium, the insulation reliability of the material deteriorates. Additionally, it has been reported that in alumina used in secondary batteries, impurities such as calcium cause a problem of increased resistivity.
[0007] Accordingly, techniques for reducing impurities in alumina powder have been proposed in the past. For example, Patent Document 1 proposes a method for producing α-alumina by grinding aluminum hydroxide or transition alumina by the Bayer method and then calcining it at a temperature of 600 to 1400°C in an atmosphere gas containing hydrogen chloride gas (Claim 1 of Patent Document 1). In addition, Patent Document 1 describes obtaining high-purity α-alumina with a sodium content of 40 ppm or less and an iron content of 20 ppm or less, and obtaining α-alumina with a reduced calcium content by washing the α-alumina after calcination (
[0017] and
[0037] of Patent Document 1).
[0008] Patent Document 2 discloses a method for producing α-alumina by using a calcination vessel containing a predetermined amount of Al2O3 and SiO2 to calcine aluminum hydroxide obtained by the Bayer method and then washing the obtained α-alumina (Claims of Patent Document 2). In addition, Patent Document 2 describes a method for producing high-purity α-alumina with impurity metals such as Si, Fe, Ca, and Na removed as much as possible by introducing α-alumina into repulping water to form a slurry and washing it by stirring, and then washing it by suction filtration while passing washing water through it (
[0021] and
[0026] of Patent Document 2). Prior art literature
[0009] Japanese Patent Publication No. Hei 8-290914 and Japanese Patent Publication No. 2008-150238 The problem to be solved
[0010] As such, although methods for producing α-alumina powder with a low impurity content have been proposed in the past, there is room for improvement in the conventional methods. For example, in the method of Patent Document 1, crushed aluminum hydroxide or transition alumina is calcined in an atmosphere containing hydrogen chloride. Therefore, it is necessary to construct equipment such as a calcination furnace with materials that are not corroded by hydrogen chloride gas. In addition, in order to prevent leakage of toxic hydrogen chloride gas, it is necessary to provide airtightness to the calcination furnace, and these factors lead to an increase in manufacturing costs.
[0011] In the method proposed in Patent Document 2, alumina powder with reduced soda (Na) content can be obtained relatively simply, and in this respect, it has a certain effect. However, as investigated by the inventors, in the method of Patent Document 2, while the soda (Na) content was reduced by washing treatment, the reduction of calcium (Ca) content was not confirmed. In order to obtain alumina powder with low calcium content, it is necessary to reduce the calcium in the aluminum hydroxide, which is the raw material. To do this, it is necessary to use a sodium aluminate solution or seed with higher purity, or to research manufacturing equipment such as containers used for crystallization, which leads to the problem that these methods result in increased costs.
[0012] In addition, when a resin composition is prepared by filling a resin or rubber with alumina powder obtained by the method of Patent Document 2 as a heat dissipation filler, there were cases where the filling properties of the alumina powder deteriorated and the viscosity of the resin composition became excessively high. If the filling properties deteriorate, the uniform dispersion of the alumina powder within the resin composition is hindered, and the thermal conductivity of the product made from the resin composition is reduced. Furthermore, if the viscosity of the resin composition is excessively high, there is a concern that it will be difficult to mold this composition. In addition, the inventors investigated to determine the cause of the deterioration in filling properties and confirmed that in the method proposed in Patent Document 2, the BET specific surface area of the alumina powder increases during the washing process. It was also thought that the increase in the BET specific surface area led to the deterioration of filling properties and moldability. Furthermore, it was thought that the cause of the increase in the BET specific surface area was that the alumina powder became hydrated due to the washing process.
[0013] Under these circumstances, the inventors further investigated and found that the calcium (Ca) concentration in the powder can be reduced by a simple method of treating the α-alumina powder in an aqueous solution containing an organic silane compound having a hydrolyzable group. In addition, it was found that this treatment suppresses the hydration of the α-alumina powder and the resulting increase in the BET specific surface area.
[0014] The present invention, completed based on these findings, aims to provide a manufacturing method that enables obtaining alumina powder with reduced calcium (Ca) concentration by a simple method while suppressing the increase in BET specific surface area due to hydration. means of solving the problem
[0015] The present invention includes the following embodiments (1) to (17). In addition, the expression “to” in this specification includes numerical values at both ends. That is, “X to Y” has the same meaning as “X or more and Y or less.”
[0016] (1) A treatment process in which α-alumina raw material powder is introduced and immersed in a treatment aqueous solution containing an organic silane compound having a hydrolyzable group, thereby obtaining α-alumina powder with reduced calcium (Ca) concentration, and
[0017] A method for manufacturing α-alumina powder having an evaluation process for measuring and comparing the concentration of calcium contained in the α-alumina raw material powder and the concentration of calcium contained in the α-alumina powder.
[0018] (2) The method of (1), wherein the above treatment solution contains the above organic silane compound in a ratio of 0.10 mass% or more relative to the mass of the above α-alumina raw material powder.
[0019] (3) The method of (1) or (2), wherein the organic silane compound is at least one selected from the group consisting of alkoxysilane, vinyl group-containing silane coupling agents and epoxy group-containing silane coupling agents.
[0020] (4) In the above evaluation process, the CaO equivalent concentration (c1[f-CaO]) of the soluble calcium powder contained in the α-alumina raw material powder and the CaO equivalent concentration (c2[f-CaO]) of the soluble calcium powder contained in the α-alumina powder are measured, and the soluble calcium concentration ratio (c2[f-CaO] / c1[f-CaO]) is calculated. This is a method of any one of (1) to (3).
[0021] (5) The method of (4) in which the ratio of soluble calcium concentration (c2[f-CaO] / c1[f-CaO]) is 0.90 or less.
[0022] (6) A method of any one of (1) to (5) wherein the CaO equivalent concentration (c2[T-CaO]) of the total calcium content included in the α-alumina powder is 0.030 mass% or less, and the CaO equivalent concentration (c2[f-CaO]) of the soluble calcium content is 0.010 mass% or less.
[0023] (7) A method of any one of (1) to (6) wherein the total soda powder equivalent concentration (c2[T-Na2O]) contained in the α-alumina powder is 0.10 mass% or less, and the soluble soda powder equivalent concentration (c2[f-Na2O]) is 0.001 mass% or more and 0.015 mass% or less.
[0024] (8) A method of any one of (1) to (7) wherein the SiO2 equivalent concentration (c2[SiO2]) of the silicon powder contained in the α-alumina powder is 0.030 mass% or more and 0.500 mass% or less.
[0025] (9) A method of any one of (1) to (8) wherein the difference (|c2[SiO2]-c1[SiO2]|) between the SiO2 equivalent concentration of silicon in the α-alumina raw material powder (c1[SiO2]) and the SiO2 equivalent concentration of silicon in the α-alumina powder (c2[SiO2]) is 0.001 mass% or more.
[0026] (10) A method of any one of (1) to (9) wherein the 45 μm sieve weight of the α-alumina raw material powder is 100 ppm or less.
[0027] (11) A method of any one of (1) to (10) wherein the average particle size (Dp50) of the α-alumina powder is 2.0 μm or more and 5.0 μm or less.
[0028] (12) A method of any one of (1) to (11) wherein the BET specific surface area of the α-alumina powder is 1.0 m² / g or more and 3.5 m² / g or less.
[0029] (13) The method of any one of (1) to (12) wherein the α-alumina powder has a span value ((Dp90-Dp10) / Dp50)) expressed as cumulative 10% diameter (Dp10), cumulative 50% diameter (Dp50), and cumulative 90% diameter (Dp90) in the particle size distribution on a mass basis, which is 2.0 or less.
[0030] (14) A method of any one of (1) to (13) having a preparation process of adding and mixing a halogen-based mineralizing agent to aluminum hydroxide obtained by the Bayer method to produce a mixture, then calcining the mixture at a temperature of 1100°C or higher and 1600°C or lower to produce a calcined product, and further crushing the calcined product to produce the α-alumina raw material powder.
[0031] (15) The method of (14) in which the total soda content in the aluminum hydroxide is converted to Na2O concentration (c0[T-Na2O]) of 0.3 mass% or less.
[0032] (16) The method of (14) or (15) of the above, wherein the above mixture is filled into a firing vessel made of silica-containing alumina ceramics and fired, and the above mixture is fired, and the molding density at a molding pressure of 98.07 MPa is 2.05 g / cm³ or more, and the BET specific surface area is 0.9 m² / g or less.
[0033] (17) When the above calcined product is crushed to produce the above α-alumina raw material powder, the BET equivalent diameter (D of the above calcined product) BET The ratio of the average particle size (Dav) of the above α-alumina raw material powder to ) (Dav / D BET A method of any one of (14) to (16) for crushing a calcined product under conditions where ) falls within the range of 1.0 or more and 2.0 or less. Effects of the invention
[0034] According to the present invention, a manufacturing method is provided that enables obtaining an alumina powder with reduced calcium (Ca) concentration in a simple manner while suppressing the increase in BET specific surface area due to hydration. Specific details for implementing the invention
[0035] Specific embodiments of the present invention (hereinafter referred to as "the present embodiments") will be described. Furthermore, the present invention is not limited to the following embodiments, and various modifications are possible within the scope of not altering the gist of the present invention.
[0036] <<Method for Manufacturing α-Alumina Powder>>
[0037] The method for manufacturing α-alumina powder according to the present embodiment comprises a treatment process in which α-alumina raw material powder is introduced and immersed in a treatment aqueous solution containing an organic silane compound having a hydrolyzable group, thereby obtaining α-alumina powder with a reduced calcium (Ca) concentration, and an evaluation process in which the calcium concentration contained in the α-alumina raw material powder and the calcium concentration contained in the α-alumina powder are measured and compared. Additionally, if necessary, the manufacturing method according to the present embodiment may further comprise a preparation process in which a halogen-based mineralizing agent is added to and mixed with aluminum hydroxide obtained by the Bayer method to produce a mixture, and then the obtained mixture is calcined at a temperature of 1100°C to 1600°C to produce a calcined product, and further the obtained calcined product is crushed to produce α-alumina raw material powder. Details of each process are described below.
[0038] Preparation Process
[0039] In the preparation process, α-alumina raw material powder is first prepared. The α-alumina raw material powder is a raw material for manufacturing the final product, α-alumina powder, by processing it. The α-alumina raw material powder contains α-alumina (Al2O3) as the main component. α-alumina has a trigonal corundum-type crystal structure. It is also chemically stable and has excellent heat resistance, corrosion resistance, wear resistance, insulation, and thermal conductivity, as well as high strength and hardness. As long as α-alumina is the main component, the method of manufacturing the α-alumina raw material powder is not particularly limited. For example, it may be manufactured by the Bayer method. Alternatively, it may be manufactured by directly thermally decomposing aluminum salts such as aluminum sulfate, by reacting oxygen or water vapor with aluminum chloride vapor, or by neutralizing aluminum salts.
[0040] Suitablely, α-alumina raw material powder produced by the Bayer method is used. The Bayer method is a major method for producing α-alumina powder and has the advantage of being able to produce α-alumina powder at a low cost. In particular suitablely, a mixture is prepared by adding and mixing a halogen-based mineralizing agent to aluminum hydroxide (Al(OH)3) obtained by the Bayer method, and then the obtained mixture is calcined at a temperature of 1100°C or higher and 1600°C or lower to produce a calcined product, and the obtained calcined product is then ground to produce α-alumina raw material powder. By doing so, it becomes possible to easily obtain alumina powder with a lower impurity content, a desired average particle size, and a sharp particle size distribution.
[0041] Aluminum hydroxide is the aluminum source for α-alumina powder. The Na2O equivalent concentration (c0[T-Na2O]) of the total soda powder contained in the aluminum hydroxide is preferably 0.3 mass% or less. In addition, the average secondary particle size of the aluminum hydroxide is preferably 10 µm or more and 200 µm or less, and more preferably 30 µm or more and 150 µm or less. Here, the average secondary particle size is a value measured by a laser scattering particle size distribution analyzer. By using such aluminum hydroxide, it is possible to more reliably obtain α-alumina powder having a desired average particle size and a sharp particle size distribution.
[0042] Halogen-based mineralizing agents have the effect of promoting the crystallization of α-alumina. Examples of halogen-based mineralizing agents include fluoride-based mineralizing agents such as aluminum fluoride, sodium fluoride, cryolite, magnesium fluoride, and calcium fluoride; chloride-based mineralizing agents such as hydrogen chloride, ammonium chloride, and aluminum chloride; and iodide-based mineralizing agents such as ammonium iodide. The optimal amount of halogen-based mineralizing agent to be added varies depending on the type of mineralizing agent used. Therefore, it is difficult to determine the optimal amount to be added unconditionally. For example, in the case of fluoride-based mineralizing agents, the amount of the mineralizing agent added to the mixture is preferably 0.05 mass% or more and 1.0 mass% or less in terms of fluorine, and more preferably 0.1 mass% or more and 0.5 mass% or less.
[0043] The mixture is calcined at a temperature of 1100°C or higher and 1600°C or lower. If the calcination temperature is below 1100°C, the primary particles do not grow to the desired size, and if it exceeds 1600°C, the particles may fuse together, potentially deteriorating the handling properties of the resulting alumina powder. The calcination time is typically 1 minute or more and 24 hours or less, and preferably 1 hour or more and 20 hours or less. The calcination may be performed using a known calcination furnace, such as a continuous furnace like a tunnel kiln or a batch-type electric furnace.
[0044] Suitablely, the mixture is filled into a firing vessel made of silica-containing alumina ceramics and fired, and a fired product is produced having a molding density of 2.05 g / cm³ or more at a molding pressure of 98.07 MPa and a BET specific surface area of 0.9 m² / g or less. If the molding density is less than 2.05 g / cm³, the shape of the particles in the obtained alumina powder tends to become plate-like. Therefore, when the alumina powder is filled into a resin or rubber to produce a resin composition, there is a risk that the viscosity of the resin composition will become too high. A molding density of 2.1 g / cm³ or more and 2.5 g / cm³ or less is more preferable. In addition, in a fired product with a BET specific surface area exceeding 0.9 m² / g, particle growth due to firing is insufficient. Therefore, there is a risk that it will be difficult to obtain an alumina powder having a desired average particle size and a sharp particle size distribution. In addition, the molding density and BET specific surface area of the sintered product can be adjusted by controlling the manufacturing conditions of the α-alumina raw material powder, for example, the particle size of aluminum hydroxide, the amount of halogen-based mineralizing agent added, and / or the sintering temperature or sintering time.
[0045] The pulverization of the sintered product can be performed using known methods. For example, a vibratory mill; a container-driven medium mill such as a vibratory ball mill, a rotary ball mill, or a planetary mill; a medium-stirring mill such as an attitter; or an air-flow grinder such as a jet mill, a counter-jet mill, or a jetmizer can be used. By grinding, an α-alumina raw material powder can be obtained.
[0046] Suitablely, the BET equivalent diameter (D of the sintered product BET The ratio of the average particle size (Dav) of the α-alumina raw material powder obtained by grinding (Dav / D BET The calcined product is crushed under conditions where ) falls within the range of 1.0 to 2.0. Ratio (Dav / D BETUnder conditions where ) exceeds 2.0, insufficient grinding occurs. Consequently, the finally obtained α-alumina powder contains a large amount of cluster-like or pumice-like aggregated particles. Furthermore, these aggregated particles absorb the resin or rubber. Therefore, when α-alumina powder (calcined product) is filled into resin or rubber to produce a resin composition, there is a problem that the viscosity of the resin composition increases. BET Under conditions where ) is less than 1.0, excessive grinding occurs. Along with the generation of a large number of chipping particles (fine particles), coarse particles formed by the aggregation of chipping particles are produced, and as a result, there is a risk that it will be difficult to uniformly disperse the finally obtained α-alumina powder in the resin or rubber.
[0047] Here, the average particle size (Dav) corresponds to the 50% cumulative diameter (Dp50) in the particle size distribution based on mass (volume basis) of the α-alumina raw material powder. The particle size distribution can be measured using a laser scattering particle size distribution analyzer. In addition, the BET equivalent diameter (D BET ) is the BET specific surface area (S of the sintered product BET ) is measured, and the BET specific surface area obtained is calculated according to the following equation (1). Also, in the following equation (1), ρ is the true specific gravity of α-alumina (3.98 g / cm³).
[0048]
[0049] Processing Process
[0050] In the treatment process, the prepared α-alumina raw material powder is introduced and immersed in a treatment aqueous solution containing an organic silane compound having a hydrolyzable group. As a result, calcium (Ca) is leached into the treatment aqueous solution, and as a result, α-alumina powder with reduced calcium concentration can be obtained. In addition, since soda (Na) is also leached into the treatment aqueous solution, it becomes possible to obtain α-alumina powder with reduced soda as well as calcium. Although the detailed reason is unclear, it is presumed that impurities (Ca, Na) in the α-alumina raw material powder form a water-soluble complex with the organic silane compound, which makes it easier for the impurities to be leached into the aqueous solution.
[0051] In particular, according to the treatment of the present embodiment, the concentration of impurities (Ca, Na) attached to the surface of the alumina powder can be effectively reduced. That is, the impurities include those attached to the surface of the powder and those present inside the powder. The impurities attached to the surface of the powder are soluble components that dissolve easily in the treatment aqueous solution. Therefore, by immersing in the treatment aqueous solution, the impurities attached to the surface of the alumina powder can be easily removed.
[0052] In addition, according to the method of the present embodiment using an aqueous solution containing an organic silane compound, the hydration of the α-alumina powder can be suppressed, and an excessive increase in the BET specific surface area can be prevented. Therefore, when the obtained α-alumina powder is filled into a resin or rubber to produce a resin composition, it is possible to prevent the occurrence of problems such as deterioration in fillability and moldability due to an increase in the BET specific surface area. On the other hand, in the conventional method of removing soda (Na) by washing the α-alumina powder with water, the α-alumina powder hydrates, and the BET specific surface area becomes excessively high. Furthermore, calcium (Ca) cannot be sufficiently removed by washing with water.
[0053] The detailed reason why the hydration of the α-alumina powder is inhibited by the method of the present embodiment is unclear. However, it is presumed that an organic silane compound in the aqueous solution adsorbs to the surface of the α-alumina powder and hinders hydration through some mechanism.
[0054] In addition, according to the method of the present embodiment, since the surface of the obtained α-alumina powder is modified with silane, when this α-alumina powder is used as a heat dissipation filler to fill resin or rubber, the effect of improving compatibility and adhesion with the resin or rubber is also obtained.
[0055] In addition, in the method of the present embodiment, the α-alumina raw material powder is introduced into the treatment aqueous solution in a dry powder state. That is, if the α-alumina raw material powder is dispersed in water and slurried in advance, the powder becomes hydrated at this stage. Therefore, it is important to introduce the α-alumina raw material powder into the treatment aqueous solution in a dry powder state rather than as a slurry.
[0056] The type of organic silane compound is not limited as long as it has a hydrolyzable group. Examples include silanes or silane coupling agents. Examples of silanes include alkoxysilanes, silazanes, and siloxanes. In addition, examples of silane coupling agents include silane coupling agents containing vinyl groups, epoxy groups, styryl groups, methacrylic groups, acrylic groups, and / or amino groups. It is preferable that the organic silane compound be at least one selected from the group consisting of methylsilane, vinyl group-containing silane coupling agents, and epoxy group-containing silane coupling agents, and it is particularly preferable that it be at least one selected from the group consisting of methyltrimethoxysilane, vinyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-glycidoxypropylmethyldimethoxysilane.
[0057] The content of the organic silane compound in the treatment aqueous solution is not limited. However, the higher the content of the organic silane compound, the more effectively impurities (Ca, Na) can be removed. It is preferable that the treatment aqueous solution contains the organic silane compound at a ratio of 0.10 mass% or more relative to the mass of the α-alumina powder, more preferable that it contains it at a ratio of 0.25 mass% or more, even more preferable that it contains it at a ratio of 0.50 mass% or more, and particularly preferable that it contains it at a ratio of 1.00 mass% or more. In terms of molar amount, it is preferable that the treatment aqueous solution contains the organic silane compound at a ratio of 0.0007 mol / kg or more relative to the mass of 1 kg of α-alumina powder, more preferable that it contains it at a ratio of 0.0010 mol / kg or more, even more preferable that it contains it at a ratio of 0.0050 mol / kg or more, and particularly preferable that it contains it at a ratio of 0.0110 mol / kg or more.
[0058] On the other hand, even if the content of the organic silane compound is excessively high, the effect of removing impurities (Ca, Na) does not increase beyond that. In addition, there is a risk that silicon (Si) derived from the organic silane compound may be incorporated into the α-alumina powder in excessive amounts. The organic silane compound also acts as an adhesive for the alumina particles. Therefore, if the organic silane compound is present in large quantities, the particles in the alumina powder may aggregate. If particle aggregation occurs, it is necessary to break it up in a subsequent process, which leads to the problem that this results in an increase in the BET specific surface area of the alumina powder. The treatment aqueous solution may contain the organic silane compound in a ratio of 20.00 mass% or less relative to the mass of the α-alumina powder, may contain it in a ratio of 10.00 mass% or less, may contain it in a ratio of 5.00 mass% or less, or may contain it in a ratio of 3.00 mass% or less. In terms of molar amount, the treatment aqueous solution may contain an organic silane compound at a ratio of 1.35 mol / kg or less relative to the mass of 1 kg of α-alumina powder, 1.00 mol / kg or less, 0.68 mol / kg or less, or 0.45 mol / kg or less.
[0059] The immersion time of the α-alumina raw material powder is not limited. However, the longer the immersion time, the more effectively impurities (Ca, Na) are removed. The immersion time may be 0.5 hours or more, 1 hour or more, or 10 hours or more. On the other hand, even if the immersion time is excessively long, the effect of impurity removal does not become higher than that. In addition, there is a risk that an excessive amount of silicon (Si) derived from organosilane compounds may be incorporated into the α-alumina powder. The immersion time may be 100 hours or less, 50 hours or less, or 30 hours or less.
[0060] As long as the α-alumina raw material powder is immersed in the treatment aqueous solution, the treatment method is not limited. The treatment aqueous solution into which the α-alumina raw material powder has been added may be left standing or stirred. However, it is preferable to proceed with the treatment while stirring the treatment aqueous solution. This is because stirring promotes the leaching of impurities (Ca, Na) into the treatment aqueous solution.
[0061] Through such treatment, α-alumina powder with reduced calcium (Ca) and soda (Na) concentrations can be obtained. Before the subsequent evaluation process, the obtained α-alumina powder can be recovered from the treated aqueous solution and further dried. Recovery can be performed using solid-liquid separation methods such as filtration or centrifugation. Additionally, drying can be performed at a temperature at which the α-alumina powder does not grow, for example, between 80°C and 600°C. Furthermore, the α-alumina powder may be crushed after drying.
[0062] Evaluation Process
[0063] In the evaluation process, the concentration of calcium (Ca) contained in the α-alumina raw material powder and the concentration of calcium (Ca) contained in the α-alumina powder are measured and compared. By establishing this process, the degree of reduction in calcium concentration during the treatment process can be accurately estimated.
[0064] As long as the calcium concentration is measurable, the measurement method is not limited. For example, a fluorescence X-ray analyzer, an atomic absorption spectrophotometer, and / or an ICP emission spectrophotometer may be used. Furthermore, the comparison method is not particularly limited. For example, the difference between the calcium concentration contained in the α-alumina raw material powder and the calcium concentration contained in the α-alumina powder may be calculated, and the evaluation may be based on the magnitude of this difference. Alternatively, the ratio between the calcium concentration contained in the α-alumina raw material powder and the calcium concentration contained in the α-alumina powder may be calculated, and the evaluation may be based on the magnitude of this ratio. The comparison may be performed automatically or manually. For example, a method in which the measurement value is transmitted from the analysis device to a computer and automatically interpreted may be used.
[0065] Suitably, the CaO equivalent concentration of soluble calcium contained in the α-alumina raw material powder (c1[f-CaO]) and the CaO equivalent concentration of soluble calcium contained in the α-alumina powder (c2[f-CaO]) are measured, and the soluble calcium concentration ratio (c2[f-CaO] / c1[f-CaO]) is calculated. Also suitably, the CaO equivalent concentration of the total calcium contained in the α-alumina raw material powder (c1[T-CaO]) and the CaO equivalent concentration of the total calcium contained in the α-alumina powder (c2[T-CaO]) are measured. The soluble calcium concentration ratio (c2[f-CaO] / c1[f-CaO]) is preferably 0.90 or less, more preferably 0.80 or less, and even more preferably 0.65 or less. The total calcium concentration ratio (c2[T-CaO] / c1[T-CaO]) is preferably 0.97 or less, more preferably 0.95 or less, and even more preferably 0.90 or less.
[0066] As described above, the impurities (Ca, Na) contained in the alumina powder include soluble impurities attached to the surface of the powder and impurities present inside the powder. The concentration of soluble calcium (c[f-CaO]) is the concentration of calcium attached to the surface of the powder. Furthermore, the total calcium concentration (c[T-CaO]) is the sum of the concentration of calcium attached to the surface of the powder and calcium present inside the powder. By using the soluble calcium concentration ratio (c2[f-CaO] / c1[f-CaO]) and the total calcium concentration ratio (c2[T-CaO] / c1[T-CaO]) as indicators, the degree of reduction of soluble calcium attached to the surface of the powder or the total calcium can be accurately estimated.
[0067] In addition, the soluble calcium concentration (c1[f-CaO], c2[f-CaO]) can be determined by adding the alumina powder to water, heating it to dissolve the calcium into the water, and analyzing the calcium concentration in the water after dissolution using ICP emission spectroscopy. In addition, the total calcium concentration (c1[T-CaO]) of the α-alumina raw material powder can be determined by fluorescence X-ray analysis. In addition, the total calcium concentration (c2[T-CaO]) of the α-alumina powder can be calculated according to the following equation (2).
[0068]
[0069] Judgment Process
[0070] If necessary, a judgment process may be provided after the evaluation process. In the judgment process, acceptable and unacceptable products are determined based on the calcium concentration of the obtained α-alumina powder or the amount of reduction thereof. For example, α-alumina powder in which the soluble calcium concentration (c2[f-CaO]) or the total calcium concentration (c2[f-CaO]) is less than or equal to a predetermined value is judged as acceptable, and other powders are judged as unacceptable.
[0071] According to the method of the present embodiment, an α-alumina powder with reduced impurity (Ca, Na) concentration can be obtained. The CaO equivalent concentration (c2[T-CaO]) of the total calcium content included in the α-alumina powder is preferably 0.030 mass% or less, and more preferably 0.020 mass% or less. In addition, the CaO equivalent concentration (c2[f-CaO]) of the soluble calcium content is preferably 0.010 mass% or less, and more preferably 0.006 mass% or less. Furthermore, the Na2O equivalent concentration (c2[T-Na2O]) of the total soda content included in the α-alumina powder is preferably 0.10 mass% or less, and more preferably 0.08 mass% or less. The Na2O equivalent concentration of soluble soda (c2[f-Na2O]) is preferably 0.001 mass% or more and 0.015 mass% or less, and more preferably 0.001 mass% or more and 0.012 mass% or less. In addition, the concentration of soluble soda can be determined by atomic absorption analysis. In addition, the concentration of the total soda can be determined by fluorescence X-ray analysis.
[0072] The SiO2 equivalent concentration (c2[SiO2]) of silicon contained in the α-alumina powder is preferably 0.030 mass% or more and 0.500 mass% or less, and more preferably 0.040 mass% or more and 0.400 mass% or less. Generally, the α-alumina powder contains silicon (Si) derived from raw materials or the calcination process as an impurity in an amount of about 0.01 to 0.03 mass%. In the manufacturing method of the present embodiment, the concentration of silicon is increased by undergoing a treatment process using an organic silane compound. By using the silicon concentration in the α-alumina powder as an indicator, it becomes possible to sufficiently secure the effect of the organic silane compound treatment. In addition, the silicon concentration can be determined by the molybdenum blue absorption spectrophotometry using a double-beam spectrophotometer.
[0073] The difference (|c2[SiO2]-c1[SiO2]|) between the SiO2 equivalent concentration of silicon contained in the α-alumina raw material powder (c1[SiO2]) and the SiO2 equivalent concentration of silicon contained in the α-alumina powder (c2[SiO2]) is preferably 0.001 mass% or more, more preferably 0.002 mass% or more, and even more preferably 0.003 mass% or more. By using the increase in the silicon concentration in the α-alumina powder as an indicator, it becomes possible to sufficiently secure the effect of the organic silane compound treatment. However, since the organic silane compound is used for cleaning, there is no need to fix it to the alumina after treatment.
[0074] The 45㎛ sieve content of the α-alumina raw material powder is preferably 100 ppm or less, and more preferably 50 ppm or less. The 45㎛ sieve content serves as a standard for the amount of coarse particles in the α-alumina raw material powder. If the α-alumina raw material powder contains a large amount of coarse particles, the amount of coarse particles in the finally obtained α-alumina powder increases. Consequently, when the α-alumina powder is filled into a resin or rubber to produce a resin composition, and this resin composition is molded to produce a molded product, there is a risk that the coarse particles will form protrusions protruding from the surface of the product. If such protrusions occur, it becomes difficult to bring the product into close contact with other components, such as a heat source, which may lead to problems such as poor heat dissipation. Therefore, it is preferable for the 45㎛ sieve content to be low.
[0075] In addition, the 45㎛ sieve weight can be obtained by sieving the α-alumina powder using a JIS Z8801-1 test sieve (mesh size 45㎛). In addition, the span value can be obtained from the particle size distribution measured using a laser scattering particle size distribution meter. Specifically, it is obtained according to the following equation (3) by using the cumulative 10% diameter (Dp10), cumulative 50% diameter (Dp50), and cumulative 90% diameter (Dp90) in the particle size distribution on a mass basis (volume basis).
[0076]
[0077] The average particle size (Dp50) of the finally obtained α-alumina powder is preferably 2.0 μm or more and 5.0 μm or less, and more preferably 2.5 μm or more and 4.0 μm or less. If the particle size of the α-alumina powder is excessively small, the viscosity of the resin composition produced by filling the resin or rubber with this α-alumina powder becomes too high, which may make molding difficult. Furthermore, even if molding is possible, the filling ability of the α-alumina powder in the composition deteriorates, and there is a risk that the thermal conductivity of the product made from this resin composition will decrease. Therefore, from the perspective of moldability, filling ability, and thermal conductivity, it is desirable for the particle size of the α-alumina powder to be appropriately large. On the other hand, there is an upper limit to the particle size of the α-alumina powder produced by the Bayer method due to reasons related to the manufacturing method.
[0078] The BET specific surface area of the α-alumina powder is preferably 1.0 m² / g or more and 3.5 m² / g or less, and more preferably 1.2 m² / g or more and less than 2.7 m² / g. As the BET specific surface area increases, the particle size of the powder decreases. From the perspective of moldability, packing ability, and thermal conductivity, it is desirable for the BET specific surface area of the α-alumina powder to be appropriately small.
[0079] The span value ((Dp90-Dp10) / Dp50)) of the α-alumina powder is preferably 2.0 or less, and more preferably 1.6 or less. If the span value is excessively large, the particle size distribution becomes too broad. When the α-alumina powder is used as a heat dissipation filler, problems arise such as deterioration of thermal conductivity and difficulty in uniform dispersion of the filler. Furthermore, when the α-alumina powder is applied to an application requiring a specific particle size distribution, problems arise such as difficulty in designing the particle size distribution. Therefore, a smaller span value is preferable.
[0080] According to the manufacturing method of the present embodiment, it is possible to obtain α-alumina powder with reduced calcium (Ca) concentration while suppressing the increase in BET specific surface area due to hydration in a simple manner. Such α-alumina powder is useful for known applications such as structural members, tools, abrasives, fillers, spark plugs, insulators, electronic substrates, and refractories. In particular, when applied as a heat dissipation filler to fill resins or rubber, it is possible to obtain a product with excellent thermal conductivity without causing problems such as deterioration of fillability and moldability.
[0081] Examples
[0082] The present invention will be explained in more detail using the following examples. However, the present invention is not limited to the following examples.
[0083] <<Experimental Examples A and B>>
[0084] In Experimental Example A, treatment was performed using 3-glycidoxypropylmethyldimethoxysilane or 3-glycidoxypropyltrimethoxysilane, which are epoxy group-containing silane coupling agents, as the organic silane compound, and the effect was investigated. In addition, the effect of adding acetic acid together with the organic silane compound was also investigated. In addition, in Experimental Example B, treatment was performed using vinyltrimethoxysilane, which is a vinyl group-containing silane coupling agent, as the organic silane compound, and the effect was investigated.
[0085] (1) Preparation of α-alumina powder
[0086] [Comparative Example A1]
[0087] <Production of α-alumina raw material powder>
[0088] First, aluminum hydroxide obtained by the Bayer method (Nippon Gekinzoku Co., Ltd., B52) was prepared. This aluminum hydroxide had an average secondary particle size of 55 μm and a total soda equivalent Na2O concentration (c0[T-Na2O]) of 0.2 mass%. Next, aluminum fluoride was added to the prepared aluminum hydroxide as a halogen-based mineralizing agent at a ratio of 0.4 mass% in terms of alumina equivalent, and then mixed to obtain a mixture. The obtained mixture was filled into a silica-containing alumina ceramic firing vessel and fired using a tunnel kiln at 1500°C ± 10°C for about 15 hours.
[0089] Subsequently, the obtained calcined material was ground to produce an α-alumina raw material powder as the ground material. For grinding, a rotary ball mill (manufactured by Chuko Seiki Co., Ltd.) was used, filled with 20 mmφ alumina balls equivalent to 44 volume% of the internal volume of the ball mill. In addition, the amount of calcined material charged was set to 0.18 kg per liter of the internal volume of the ball mill. Furthermore, the average particle size (Dav) after grinding was 3.0 μm, and the average particle size (Dav) after grinding and the BET equivalent diameter (D) before grinding BET )'s particle size ratio (Dav / D BET The powder was ground so that the value was 1.10 or higher and 1.45 or lower. The obtained α-alumina raw material powder was evaluated as is without treatment using an organic silane compound.
[0090] [Example A1]
[0091] In Example A1, α-alumina powder was prepared by treating the α-alumina raw material powder obtained in Comparative Example A1 with an organic silane compound. As the organic silane compound, 3-glycidoxypropylmethyldimethoxysilane ((CH3O)2CH3SiC6H 11 O2) was used. The specific procedure was as follows.
[0092] Processing Process
[0093] 3-glycidoxypropylmethyldimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-402, molecular weight 220.3) was placed in a polypropylene container containing pure water, and then stirred for 1 hour using a Teflon (registered trademark) stirring blade to prepare a treatment aqueous solution. At this time, the amount of 3-glycidoxypropylmethyldimethoxysilane added to the aqueous solution was adjusted to be 0.25 mass% (0.011 mol / kg per 1 kg mass of α-alumina raw material powder) relative to the mass of the added α-alumina raw material powder.
[0094] Next, 100g of α-alumina raw material powder was added to 100g of the prepared treatment solution in its dry state and stirred at room temperature for 20 hours. Afterward, solid-liquid separation was performed on the aqueous solution using a Buchner funnel, the obtained solid was dried at 110°C for one full day, and then crushed using a mortar and pestle to obtain α-alumina powder.
[0095] [Example A2]
[0096] In Example A2, 3-glycidoxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-403, molecular weight 236.3) was used instead of 3-glycidoxypropylmethyldimethoxysilane. In addition, the amount of 3-glycidoxypropyltrimethoxysilane added was adjusted to 0.25 mass% (0.011 mol / kg per 1 kg mass of α-alumina raw material powder) relative to the mass of the α-alumina raw material powder. Except for this, the α-alumina powder was prepared in the same manner as in Example A1.
[0097] [Example A3]
[0098] In Example A3, when preparing the treatment aqueous solution, an organic silane compound (3-glycidoxypropyltrimethoxysilane) was added to pure water, and then acetic acid was added to adjust the pH of the aqueous solution to 4, and the mixture was stirred for 1 hour. Except for this, the process was carried out in the same manner as in Example A2 to produce an α-alumina powder.
[0099] [Comparative Example B1]
[0100] An α-alumina raw material powder was prepared in the same procedure as Comparative Example A1. The obtained α-alumina raw material powder was evaluated as is without treatment using an organic silane compound.
[0101] [Example B1]
[0102] In Example B1, the α-alumina raw material powder prepared in Comparative Example B1 was treated with an organic silane compound. In addition, vinyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-1003, molecular weight 148.2) was used as the organic silane compound. The amount of vinyltrimethoxysilane added was adjusted to 0.25 mass% (0.017 mol / kg per 1 kg mass of α-alumina raw material powder) relative to the mass of the α-alumina raw material powder. Except for this, the α-alumina powder was prepared in the same manner as in Example A1.
[0103] (2) Evaluation
[0104] For aluminum hydroxide, calcined product, pulverized product (α-alumina raw material powder), and α-alumina powder, various characteristics were evaluated in the following order.
[0105] <Component Analysis>
[0106] The concentrations of total calcium and total soda contained in the α-alumina raw material powder and the α-alumina powder were determined by fluorescence X-ray analysis. Specifically, the fluorescence X-ray intensity of the sample was measured using a fluorescence X-ray analyzer (Rigaku Inc. ZSX100e), and the total calcium concentration (c[T-CaO]) and total soda concentration (c[T-Na2O]) in the sample were determined using the obtained data and calibration curve. In addition, the total calcium concentration (c0[T-CaO]) in the raw aluminum hydroxide was also determined by the same method.
[0107] In addition, the concentrations of soluble calcium and soluble soda contained in the α-alumina raw powder and the α-alumina powder were determined by atomic absorption spectroscopy. Specifically, water was added to the sample such that the mass ratio of the sample to water was 1:60, and the soluble calcium and soluble soda in the sample were dissolved into the water by heating in a water bath for 30 minutes using boiling water. Subsequently, the concentration of soluble calcium (c[f-CaO]) was measured using an ICP emission spectrophotometer (Hitachi High-Tech Sciences, Inc., PS3520UVDD). In addition, the concentration of soluble soda (c[f-Na2O]) was determined using an atomic absorption spectrophotometer (Hitachi High-Techs, Inc., Z-2000). At this time, measurements were performed under the conditions of measurement mode: atomic absorption, measurement wavelength range: 589.0 nm.
[0108] In addition, the concentration of silicon (c[SiO2]) contained in the α-alumina raw material powder and the α-alumina powder was determined by quantitative analysis using the molybdenum blue absorption spectrophotometry method with a double beam spectrophotometer (Hitachi Seisakusho Inc., U-3010).
[0109] <Molding Density>
[0110] The molding density of the sintered product was measured in the following order. First, a piece was produced by press-forming the sintered product at a pressure of 98.07 MPa using a hydraulic 20-ton compression tester (Maekawa Shikenki Seisakusho Co., Ltd.). The dimensions of the obtained piece were 40 mm × 20 mm × 10 mm. Next, the mass of the piece was measured, and the molding density was calculated using the volume and mass of the piece.
[0111] <BET 비표면적>
[0112] The BET specific surface area of the calcined product, α-alumina raw material powder (pulverized product), and α-alumina powder was measured by the N2 gas adsorption method using an automatic specific surface area measuring device (Micromeritis, Flosorb II 2300 type).
[0113] <45㎛ sieve weight>
[0114] The α-alumina raw material powder (crushed material) was sieved using a JIS Z8801-1 test sieve (mesh size: 45㎛). Then, the mass of the residue remaining on the sieve was measured, and the mass of the residue obtained was divided by the total mass to calculate the amount of the 45㎛ sieve.
[0115] Particle Size Distribution
[0116] The particle size distribution of the α-alumina raw material powder was measured using a laser scattering particle size analyzer (Nikkiso Co., Ltd., Microtrac 9320HRA (×100)). Then, the 10% cumulative diameter (Dp10), 50% cumulative diameter (Dp50), and 90% cumulative diameter (Dp90) were calculated for the particle size distribution based on mass (volume). Then, using Dp10, Dp50, and Dp90, the span value was calculated according to the following equation (3).
[0117]
[0118] (3) Evaluation results
[0119] The characteristics of the α-alumina raw material powder obtained in Comparative Example A1 and Comparative Example B1, along with the characteristics of the raw aluminum hydroxide and the calcined product, are shown in Table 1. It was confirmed that the obtained α-alumina raw material powder has the desired characteristics (BET specific surface area, 45 μm sieve area, and span value).
[0120] In addition, the characteristics of the α-alumina powder are shown in Table 2. The samples treated with an organic silane compound (Examples A1 to A3 and Example B1) showed reduced calcium and soda concentrations compared to the samples not treated with an organic silane compound (Comparative Examples A1 and B1). Furthermore, the increase in BET specific surface area was suppressed, indicating that the progress of hydration was inhibited.
[0121]
[0122]
[0123] <<Experimental Example C>>
[0124] In Experimental Example C, treatment was performed using vinyltrimethoxysilane, a vinyl group-containing silane, as the organic silane compound, and the effect of its concentration was investigated (Examples C1 to C4). Additionally, for comparison, a sample not treated with an organic silane compound (Comparative Example C1) and a sample treated only with water without using an organic silane compound (Comparative Example C2) were prepared and evaluated.
[0125] (1) Preparation of α-alumina powder
[0126] [Comparative Example C1]
[0127] <Production of α-alumina raw material powder>
[0128] An α-alumina raw material powder was prepared in the same procedure as Comparative Example A1. The obtained α-alumina raw material powder was evaluated as is without treatment using an organic silane compound.
[0129] [Comparative Example C2, Examples C1 to C4]
[0130] In Comparative Example C2 and Examples C1 to C4, α-alumina powder was prepared by treating the α-alumina raw material powder obtained in Comparative Example C1 with an organic silane compound. Vinyltrimethoxysilane ((CH3O)3SiCH3=CH2; vinyl group-containing silane) was used as the organic silane compound. The specific procedure was as follows.
[0131] Processing Process
[0132] Vinyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-1003, molecular weight 148.2) was placed in a polypropylene container containing pure water, and then stirred for 1 hour using a Teflon (registered trademark) stirring blade to prepare a treatment aqueous solution. At this time, the amount of vinyltrimethoxysilane added to the aqueous solution was adjusted so that it was the value shown in Table 3 with respect to the mass of the added α-alumina raw material powder.
[0133] Next, 100g of α-alumina raw material powder was added to 100g of the prepared treatment solution in its dry state, and the mixture was stirred at room temperature for 20 hours. Afterward, solid-liquid separation was performed on the treatment solution using a Buchner funnel, and the obtained solid was dried at 110°C for one full day and then crushed with a mortar and pestle to obtain α-alumina powder. In addition, in Comparative Example C2, the α-alumina raw material powder was treated in pure water that does not contain vinyltrimethoxysilane.
[0134] (2) Evaluation
[0135] For aluminum hydroxide, calcined product, α-alumina raw material powder (pulverized product) and α-alumina powder, various characteristics were evaluated in the same manner as in Experimental Example A.
[0136] (3) Evaluation results
[0137] The characteristics of the α-alumina raw material powder obtained in Comparative Example C1 are shown in Table 1 along with the characteristics of the raw aluminum hydroxide and the calcined product. It was confirmed that the obtained α-alumina raw material powder has the desired characteristics (BET specific surface area, 45 μm sieve area, and span value).
[0138] The characteristics of the α-alumina powder are shown in Table 3. Samples treated with an organic silane compound (Examples C1 to C4) showed reduced calcium and soda concentrations compared to samples not treated with an organic silane compound (Comparative Example C1), and the effect was particularly pronounced in the region where the amount of organic silane compound added was 0.5 mass% or more. In addition, the increase in BET specific surface area was suppressed in Examples C1 to C4. In contrast, in the sample treated with only pure water (Comparative Example C2), the soda concentration was reduced, but no reduction in calcium concentration was confirmed. In addition, the BET specific surface area was significantly higher.
[0139]
[0140] <<Experimental Example D>>
[0141] In Experimental Example D, treatment was performed using 3-glycidoxypropyltrimethoxysilane, an epoxy group-containing silane, as the organic silane compound, and the effect of its concentration was investigated (Examples D1 to D4). In addition, for comparison, a sample not treated with an organic silane compound (Comparative Example D1) and a sample treated only with water without using an organic silane compound (Comparative Example D2) were prepared and evaluated.
[0142] (1) Preparation of α-alumina powder
[0143] [Comparative Example D1]
[0144] <Production of α-alumina raw material powder>
[0145] First, aluminum hydroxide obtained by the Bayer method (Nippon Gekinzoku Co., Ltd., B52) was prepared. This aluminum hydroxide had an average secondary particle size of 55 μm and a total soda equivalent Na2O concentration (c0[T-Na2O]) of 0.2 mass%. Next, aluminum fluoride was added to the prepared aluminum hydroxide as a halogen-based mineralizing agent at a ratio of 0.4 mass% in terms of alumina equivalent, and then mixed to obtain a mixture. The obtained mixture was filled into a silica-containing alumina ceramic firing vessel and fired using a tunnel kiln at 1500°C ± 10°C for about 15 hours.
[0146] Subsequently, the calcined material was ground to produce an α-alumina raw material powder as the ground material. For the grinding, a rotary ball mill (manufactured by Chuko Seiki Co., Ltd.) was used, filled with 20 mmφ alumina balls equivalent to 44 volume% of the internal volume of the ball mill. In addition, the amount of calcined material charged was set to 0.18 kg per liter of the internal volume of the ball mill. Furthermore, the average particle size (Dav) after grinding was 3.0 μm, and the average particle size after grinding (Dav) and the BET equivalent diameter (D) before grinding BET )'s particle size ratio (Dav / D BETThe powder was ground so that the value was 1.10 or higher and 1.45 or lower. The obtained α-alumina raw material powder was evaluated as is without treatment using an organic silane compound.
[0147] [Comparative Example D2, Examples D1 to D4]
[0148] In Comparative Example D2 and Examples D1 to D4, α-alumina powder was prepared by treating the α-alumina raw material powder obtained in Comparative Example D1 with an organic silane compound. As the organic silane compound, 3-glycidoxypropyltrimethoxysilane ((CH3O)3SiC6H 11 O2); an epoxy group-containing silane coupling agent was used. The specific procedure was as follows.
[0149] Processing Process
[0150] 3-glycidoxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., KBM-403, molecular weight 236.3) was placed in a polypropylene container containing pure water, and then stirred for 1 hour using a Teflon (registered trademark) stirring blade to prepare a treatment aqueous solution. At this time, the amount of 3-glycidoxypropyltrimethoxysilane added to the aqueous solution was adjusted to the value shown in Table 4 with respect to the mass of the added α-alumina raw material powder.
[0151] Next, 100g of α-alumina raw material powder was added to 100g of the prepared treatment solution in its dry state and stirred at room temperature for 20 hours. Afterwards, solid-liquid separation was performed on the treatment solution using a Buchner funnel, and the obtained solid was dried at 110°C for 1 full day and then crushed with a mortar and pestle to obtain α-alumina powder. In addition, in Comparative Example D2, the α-alumina raw material powder was treated in pure water that does not contain 3-glycidoxypropyltrimethoxysilane.
[0152] (2) Evaluation
[0153] For aluminum hydroxide, calcined product, ground product (α-alumina raw material powder) and α-alumina powder, various characteristics were evaluated in the same manner as in Experimental Example A.
[0154] (3) Evaluation results
[0155] The characteristics of the α-alumina raw material powder obtained in Comparative Example D1 are shown in Table 1 along with the characteristics of the raw aluminum hydroxide and the calcined product. It was confirmed that the obtained α-alumina raw material powder has the desired characteristics (BET specific surface area, 45 μm sieve area, and span value).
[0156] The characteristics of the α-alumina powder are shown in Table 4. Samples treated with an organic silane compound (Examples D1 to D4) showed reduced calcium and soda concentrations compared to the sample not treated with an organic silane compound (Comparative Example D1), and the effect was particularly pronounced in the region where the amount of organic silane compound added was 1.0 mass% or more. In addition, the increase in BET specific surface area was suppressed regardless of the amount of organic silane compound added. On the other hand, in the sample treated with only pure water (Comparative Example D2), the soda concentration was reduced, but the reduction in calcium concentration was very slight. In addition, the BET specific surface area was significantly higher.
[0157]
[0158] <<Experimental Example E>>
[0159] In Experimental Example E, treatment was performed using sugar instead of an organosilane compound, and the effect was investigated. It is widely known that calcium oxide (CaO) exhibits high solubility in aqueous solutions of sugars such as glucose or xylose. Therefore, it was expected that alumina powder with reduced calcium concentration could be obtained by performing treatment using sugar.
[0160] (1) Preparation of α-alumina powder
[0161] [Comparative Example E1]
[0162] An α-alumina raw material powder was prepared in the same procedure as Comparative Example A1. The obtained α-alumina raw material powder was evaluated as is without any treatment.
[0163] [Comparative Example E2]
[0164] In Comparative Example E2, α-alumina powder was prepared by treating the α-alumina raw material powder obtained in Comparative Example E1 with an aqueous solution of sugar. D-(+)-glucose and anhydrous glucose were used as the sugar. The specific procedure was as follows.
[0165] Processing Process
[0166] D-(+)-glucose, anhydrous (Alfa Aesar, Cat No. A16828, molecular weight 180.16) was placed in a polypropylene container containing pure water, and then stirred for 1 hour using a Teflon (registered trademark) stirring blade to prepare a treatment aqueous solution. At this time, the amount of D-(+)-glucose, anhydrous added to the aqueous solution was adjusted to 1.0 mass% (0.566 mol / kg per 1 kg mass of α-alumina raw material powder) relative to the mass of the added α-alumina raw material powder.
[0167] Next, 100g of α-alumina raw material powder in its dry state was added to 100g of the prepared treatment aqueous solution and stirred at room temperature for 20 hours. Afterward, solid-liquid separation was performed on the aqueous solution using a Buchner funnel, washed with 100g of pure water, and the obtained solid was dried at 110°C for one full day and then crushed in a mortar to obtain α-alumina powder.
[0168] (2) Evaluation
[0169] For aluminum hydroxide, calcined product, ground product (α-alumina raw material powder), and α-alumina powder, various characteristics were evaluated in the same manner as in Experimental Example A.
[0170] (3) Evaluation results
[0171] The characteristics of the α-alumina raw material powder obtained in Comparative Example E1 are shown in Table 1 along with the characteristics of the raw aluminum hydroxide and the calcined product. It was confirmed that the obtained α-alumina raw material powder has the desired characteristics (BET specific surface area, 45 μm sieve area, and span value).
[0172] The characteristics of the α-alumina powder are shown in Table 5. In the sample treated with sugar (D-(+)-glucose) (Comparative Example E2), the soda concentration was reduced compared to the untreated sample (Comparative Example E1), but almost no reduction in calcium concentration was observed. In addition, the BET specific surface area was high.
[0173]
[0174] In this regard, when an aqueous solution of sugar is used, the effect of reducing calcium in alumina cannot be obtained, and it was found that this is an effect unique to the present embodiment using an organic silane compound having a hydrolyzable group.
[0175] From the above results, it is understood that according to the manufacturing method of the present embodiment, an alumina powder with reduced calcium (Ca) concentration can be obtained in a simple manner while suppressing the increase in BET specific surface area due to hydration.
Claims
Claim 1 A method for manufacturing α-alumina powder, comprising: a treatment process of introducing and immersing an α-alumina raw material powder into a treatment aqueous solution containing an organic silane compound having a hydrolyzable group, thereby obtaining an α-alumina powder with a reduced calcium (Ca) concentration; and an evaluation process of measuring and comparing the concentration of calcium contained in the α-alumina raw material powder with the concentration of calcium contained in the α-alumina powder. Claim 2 A method according to claim 1, wherein the treatment aqueous solution comprises the organic silane compound in a ratio of 0.10 mass% or more with respect to the mass of the α-alumina raw material powder. Claim 3 A method according to claim 1 or 2, wherein the organic silane compound is at least one selected from the group consisting of alkoxysilane, vinyl group-containing silane coupling agents, and epoxy group-containing silane coupling agents. Claim 4 A method according to claim 1 or 2, wherein in the evaluation process, the CaO equivalent concentration (c1[f-CaO]) of the soluble calcium content included in the α-alumina raw material powder and the CaO equivalent concentration (c2[f-CaO]) of the soluble calcium content included in the α-alumina powder are measured, and the soluble calcium concentration ratio (c2[f-CaO] / c1[f-CaO]) is calculated. Claim 5 A method according to claim 3, wherein in the evaluation process, the CaO equivalent concentration (c1[f-CaO]) of the soluble calcium content included in the α-alumina raw material powder and the CaO equivalent concentration (c2[f-CaO]) of the soluble calcium content included in the α-alumina powder are measured, and the soluble calcium concentration ratio (c2[f-CaO] / c1[f-CaO]) is calculated. Claim 6 A method according to claim 4, wherein the soluble calcium concentration ratio (c2[f-CaO] / c1[f-CaO]) is 0.90 or less. Claim 7 A method according to claim 5, wherein the soluble calcium concentration ratio (c2[f-CaO] / c1[f-CaO]) is 0.90 or less. Claim 8 A method according to claim 1 or 2, wherein the CaO equivalent concentration (c2[T-CaO]) of the total calcium content included in the α-alumina powder is 0.030 mass% or less, and the CaO equivalent concentration (c2[f-CaO]) of the soluble calcium content is 0.010 mass% or less. Claim 9 A method according to claim 1 or 2, wherein the total soda powder equivalent concentration (c2[T-Na2O]) contained in the α-alumina powder is 0.10 mass% or less, and the soluble soda powder equivalent concentration (c2[f-Na2O]) is 0.001 mass% or more and 0.015 mass% or less. Claim 10 A method according to claim 1 or 2, wherein the SiO2 equivalent concentration (c2[SiO2]) of the silicon powder included in the α-alumina powder is 0.030 mass% or more and 0.500 mass% or less. Claim 11 A method according to claim 1 or 2, wherein the difference (|c2[SiO2]-c1[SiO2]|) between the SiO2 equivalent concentration of silicon contained in the α-alumina raw material powder (c1[SiO2]) and the SiO2 equivalent concentration of silicon contained in the α-alumina powder (c2[SiO2]) is 0.001 mass% or more. Claim 12 A method according to claim 1 or 2, wherein the 45㎛ sieve mass of the α-alumina raw material powder is 100 ppm or less. Claim 13 A method according to claim 1 or 2, wherein the average particle size (Dp50) of the α-alumina powder is 2.0㎛ or more and 5.0㎛ or less. Claim 14 A method according to claim 1 or 2, wherein the BET specific surface area of the α-alumina powder is 1.0 m² / g or more and 3.5 m² / g or less. Claim 15 A method according to claim 1 or 2, wherein the α-alumina powder has a span value ((Dp90-Dp10) / Dp50)) expressed as cumulative 10% diameter (Dp10), cumulative 50% diameter (Dp50), and cumulative 90% diameter (Dp90) in the particle size distribution on a mass basis, which is 2.0 or less. Claim 16 A method according to claim 1 or 2, further comprising a preparation process of adding and mixing a halogen-based mineralizing agent to aluminum hydroxide obtained by the Bayer method to produce a mixture, then calcining the mixture at a temperature of 1100°C or higher and 1600°C or lower to produce a calcined product, and further grinding the calcined product to produce the α-alumina raw material powder. Claim 17 A method according to claim 16, wherein the total soda content equivalent to Na2O (c0[T-Na2O]) contained in the aluminum hydroxide is 0.3 mass% or less. Claim 18 A method according to claim 16, wherein when firing the above mixture, the mixture is filled into a firing vessel made of silica-containing alumina ceramics and fired, and a fired product is produced having a molding density of 2.05 g / cm³ or more at a molding pressure of 98.07 MPa and a BET specific surface area of 0.9 m² / g or less. Claim 19 In paragraph 16, when the above calcined product is crushed to produce the above α-alumina raw material powder, the BET equivalent diameter (D of the above calcined product) BET The ratio of the average particle size (Dav) of the above α-alumina raw material powder to ) (Dav / D BET A method for crushing a calcined product under conditions where ) falls within the range of 1.0 or more and 2.0 or less.
Citation Information
Patent Citations
LOW-SODA α-ALUMINA POWDER EXCELLENT IN VISCOSITY CHARACTERISTICS AND METHOD FOR PRODUCING THE SAME
JP2015166294A
Alumina particle and production method thereof, and resin composition
JP2015196628A
Spherical alumina powder and resin composition including same
WO2016017637A1
Alpha-alumina and its production
JP1996290914A
Method for production of high-purity alpha-alumina
JP2008150238A